Hybrid control of a constrained velocity unicycle with local sensing - Oikonomopoulos, Apollon S.; Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2008)
This paper introduces a hybrid control scheme for steering a non-holonomic agent with limited sensing capabilities and input constraints through a stationary but unknown workspace, occupied by arbitrarily shaped obstacles. The considered constraints (i.e. constant linear and bounded angular velocities) apply to a wide category of vehicle systems. Limited sensing is realized by a radially bounded sensing device. The proposed hybrid controller respects the kinematic constraints while guaranteeing obstacle avoidance and convergence to a specified goal configuration. In addition to the analytical guarantees, we demonstrate the effectiveness of the proposed hybrid control scheme through non-trivial computer simulations.
Keywords: Speed; Computer simulation; Vehicles; Mobile robots